Proses Pengembangan Media Pembelajaran Konten Pasar Tradisional Berbasis VR - Pratama, Yogie; Fiantika, Feny Rita; Prayogo, Prayogo (Didactical Mathematics, 2025)
Traditional markets are closely related to mathematics learning, as they provide a relevant environment for applying various mathematical concepts in a practical manner. In the field of education, various technology-based learning media have been developed, one of which is Virtual Reality (VR). This study aims to enhance students' interest in learning through Virtual Reality-based learning media featuring traditional market content applied in mathematics instruction. This research follows a Research and Development (RnD) approach using the 4D development model, which consists of four main stages: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. During the development process, the researchers utilized expert validation instruments and student questionnaires. The study population consisted of fifth-grade students at SDN Kebonagung I Sukodono, Sidoarjo, with a research sample of three students. The findings indicate that media validation by experts was categorized as "Excellent," material validation was rated as "Good," and language validation was also categorized as "Excellent." Additionally, the results from student questionnaires collected during field trials were classified as "Excellent". The study concludes that the developed Virtual Reality-based learning media received positive responses. This was evident from students' enthusiasm in engaging with the media, attentively participating in classroom learning, actively contributing, and comprehending the material presented through VR. Consequently, the learning process becomes more engaging and interactive for students.